Sporogenesis and spores of Equisetum bogotense (Equisetaceae) from mountain areas of Colombia - Rincón Baron, Edgar Javier (2013)
Studies on some reproductive traits in Equisetum species are scarce and valuable to understand species distribution. Therefore, a detailed study of the sporogenesis process and spore development in E. bogotense is presented, with an analysis of the main events during meiosis, maturation of spores, spore wall ultrastructure, orbicules and elaters. Specimens were collected from 500 to 4 500m in Cauca, Colombia. Strobili at different maturation stages were fixed, dehydrated, embedded in resin, and ultra-microtome obtained sections were stained with Toluidine blue. Observations were made with optical microscopy with differential interference contrast illumination technique (DIC), transmission and scanning electron microscopy (TEM and SEM). Ultrathin sections (70-80μm) for TEM observations were stained with uranyl acetate and lead citrate; while samples for SEM observations, were fixed, dehydrated in 2.2-dimethoxypropane and dried at critical point as in standard methods. Strobili have numerous mature sporangiophores, each one with a peltate structure, the scutellum, bearing five-six sessile sporangia attached to the axis of strobilus by the manubrium. Immature sporocytes (spore mother cells) are tightly packed within the young sporangia. The sporocytes quickly undergo meiosis, by passing the stage of archesporium and give origin to tetrads of spores. The tapetum loses histological integrity during early stages of sporogenesis, intrudes as a plasmodial mass into the cavity of the sporangium, partially surrounding premeiotic sporocytes, and then, tetrads and adult spores. The tapetum disintegrates towards the end of the sporogenesis, leaving spores free within the sporangial cavity. Spores present several cytological changes that allow them to achieve greater size and increase the number of plastids, before reaching the adult stage. Sporoderm includes three layers external to the cytoplasmic membrane of the spore cell, and they are pseudoendospore, exospore and perispore. Viewed with SEM, the exospore is smooth to rugulate, with micro perforations, while the perispore is muriform, rugate, with narrow, delicate, discontinuous, randomly distributed folds delimiting incomplete, irregular areolae, externally covered by of different size, densely distributed orbicules. These orbicules are also found all over the external face and margins of the elaters, while the internal face is smooth and lack orbicules. Viewed with TEM, the exospore is a thick layer of fine granular material, while perispore is a thinner layer of dense, separate orbicules. The elaters are composed by two layers of fibrillar material: an inner layer with longitudinally oriented fibrils and an outer, thicker and less dense layer with fibrils transversely fibrils and abundant, external orbicules. It is suggested that the processes of ontogeny and characters of the sporoderm are relatively constant in Equisetum; however, sporogenesis in E. bogotense is synchronous and this condition has been observed so far only in E. giganteum, a tropical genus also found in Colombia.